Keap1-Nrf2/ARE Pathway-based Investigation into the Mechanism of Edaravone Dexborneol in Cerebral Infarction Model Neuroprotection: Mechanism of Keap1-Nrf2/ARE pathway-based edaravone dexborneol - Yang, Xue; Wang, Bo; Wang, Youming (Cellular and Molecular Biology, 2022)
The neuroprotection of acute cerebral infarction (ACI) model by edaravone dexborneol (ED)-mediated Keap1-Nrf2/ARE signal pathway was investigated. Sham operation was set as a control to prepare the ACI model with cerebral artery occlusion. The abdominal cavity was injected with edaravone (ACI+Eda group) and ED (ACI+ED group). Then, neurological deficit scores, cerebral infarct volume, oxidative stress ability, inflammatory reaction level, and the status of the Keap1-Nrf2/ARE signal pathway of rats in all groups were explored. It was demonstrated that the neurological deficit score and cerebral infarct volume of rats in the ACI group apparently increased versus those in the Sham group (P<0.05), suggesting that the ACI model was successfully prepared. Versus those in the ACI group, the neurological deficit score and cerebral infarct volume of rats in the ACI+Eda and ACI+ED groups decreased. In contrast, the activity of cerebral oxidative stress superoxide dismutase (SOD) and glutathione-peroxidase (GSH-Px) increased. Malondialdehyde (MDA) and the expressions of cerebral inflammation indicators (interleukin (IL)-1β, IL-6, and tumor necrosis factor-α messenger ribonucleic acid (TNF-α mRNA)) and cerebral Keap1 reduced. The expressions of Nrf2 and ARE increased (P<0.05). Versus those in the ACI+Eda group, all indicators of rats in the ACI+ED group were improved more apparently and were more similar to those in the Sham group (P<0.05). The above findings suggested that both edaravone and ED could mediate Keap1-Nrf2/ARE signal pathway to play a neuroprotective role in ACI. Versus edaravone, ED improved ACI oxidative stress and inflammatory reaction level and played a neuroprotective role more apparently.